STATUS SOPIR SELAMAT DALAM KECELAKAAN KENDARAAN TUNGGAL YANG MENYEBABKAN KORBAN JIWA (PERSPEKTIF AL- JINAYAH ‘ALA AN-NAFS AL-INSANIYYAH) - Maudyna, Maudyna; Fauzi, Fahrul (UI Scholars Hub, 2021)
Vehicle accidents are one of the causes of the loss of a person's life. Vehicle accidents often occur where the driver as the party driving the vehicle survives while the passenger dies. This condition causes the driver's status to be named as a suspect in accidents that occur. This study analyzes the status of the driver who survived a single-vehicle accident that caused fatalities in the perspective of al-jinayah 'ala an-nafs al-insaniyyah. This study uses normative legal research methods with qualitative data analysis methods. The results of this study are that the crime of murder in Islamic criminal law is divided into three types: intentional murder, semi-intentional murder, and murder by mistake. The driver of a vehicle that has an accident and causes fatalities when viewed in Islamic criminal law has committed a crime of murder by mistake. That is because the element of causing death, occurred by mistake (unintentionally), and the causal relationship between the mistakes and the passenger's death has been fulfilled in the driver who survived the single-vehicle accident.